2014
DOI: 10.1111/1346-8138.12642
|View full text |Cite
|
Sign up to set email alerts
|

Elevated plasma homocysteine level is possibly associated with skin sclerosis in a series of Japanese patients with systemic sclerosis

Abstract: Homocysteine is a sulfhydryl-containing amino acid that is derived from dietary methionine, and there has been increasing evidence that elevated plasma homocysteine levels are associated with increased risk of cardiovascular diseases, including carotid, coronary and peripheral arterial disease (PAD). The association of plasma homocysteine levels with peripheral vascular involvements, such as Raynaud phenomenon (RP), digital ulcers (DU) in systemic sclerosis (SSc) patients has not been well studied. The objecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
19
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 23 publications
(60 reference statements)
2
19
1
Order By: Relevance
“…There are many previous reports which demonstrated that the serum levels of oxidative stress-related factors, such as nitric oxide, Abbreviations: ATP, adenosine triphosphate; ECs, endothelial cells; HO-1, Heme Oxygenase 1; IL-6, interleukin-6; Nox, nicotinamide adenine dinucleotide phosphate (NADPH) oxidase; Nrf2, NF-E2-related factor 2; ROS, reactive oxygen species; SSc, systemic sclerosis; TGF-β, transforming growth factor-β; TNF-α, tumor necrosis factor-α; Trx2, thioredoxin 2; TUNEL, terminal deoxynucleotide transferase dUTP nick end-labeling. malondialdehyde, asymmetric dimethylarginine, hydroperoxide, and homocysteine, increased in patients with SSc [4,5]. Antioxidative biomarkers, such as superoxide dismutase and vitamin C, were lower in the serum of patients with SSc compared to healthy controls [4].…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…There are many previous reports which demonstrated that the serum levels of oxidative stress-related factors, such as nitric oxide, Abbreviations: ATP, adenosine triphosphate; ECs, endothelial cells; HO-1, Heme Oxygenase 1; IL-6, interleukin-6; Nox, nicotinamide adenine dinucleotide phosphate (NADPH) oxidase; Nrf2, NF-E2-related factor 2; ROS, reactive oxygen species; SSc, systemic sclerosis; TGF-β, transforming growth factor-β; TNF-α, tumor necrosis factor-α; Trx2, thioredoxin 2; TUNEL, terminal deoxynucleotide transferase dUTP nick end-labeling. malondialdehyde, asymmetric dimethylarginine, hydroperoxide, and homocysteine, increased in patients with SSc [4,5]. Antioxidative biomarkers, such as superoxide dismutase and vitamin C, were lower in the serum of patients with SSc compared to healthy controls [4].…”
Section: Introductionmentioning
confidence: 93%
“…Almost all patients present Raynaud's phenomenon as an initial symptom, and frequently show other manifestations of vascular diseases, including ischemic digital ulcers, pulmonary arterial hypertension, and renal arterial involvement associated with malignant hypertension and renal failure. Although the pathogenesis of SSc remains unknown, it has been elucidated that vasculopathyinduced hypoxia and oxidative stress play an important role in the prognosis of SSc [3][4][5][6][7][8]. Vasculopathy in patients with SSc is characterized by the activation of endothelial cells (ECs) and altered vascular tone.…”
Section: Introductionmentioning
confidence: 99%
“…Hypoxia and oxidative stress are also induced by ischemia and reperfusion injury after Raynaud's phenomenon (Simonini et al, 2000;Uchiyama et al, 2015). Many previous studies have reported that serum levels of oxidative stress-related factors were enhanced in SSc patients (Luo et al, 2017;Motegi et al, 2014). In addition, mice treated with agents that induce the release of free radicals, such as hydroxyl radicals and peroxynitrites, exhibited cutaneous and lung fibrosis (Servettaz et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Systemic sclerosis (SSc) is a connective tissue disease characterized by the fibrosis of the skin and internal organs, microangiopathy and autoimmunity . SSc patients develop various microangiopathies, such as Raynaud's phenomenon (RP), nail fold capillary abnormality, persistent digital ischemia, acro‐osteolysis (AO) and digital ulcers (DU) . RP and nail fold capillary abnormality generally precede the onset of fibrosis by several months or years, suggesting that vascular disorder may be a primary event in the pathogenesis of SSc .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] SSc patients develop various microangiopathies, such as Raynaud's phenomenon (RP), nail fold capillary abnormality, persistent digital ischemia, acro-osteolysis (AO) and digital ulcers (DU). 2,3,[5][6][7] RP and nail fold capillary abnormality generally precede the onset of fibrosis by several months or years, suggesting that vascular disorder may be a primary event in the pathogenesis of SSc. 2,3 Increasing evidence suggests that injury and damage of microvascular endothelial cells (EC) may occur in early SSc, leading to the proliferation of the intima, vessel narrowing and obliteration.…”
Section: Introductionmentioning
confidence: 99%